2009
DOI: 10.1111/j.1939-1676.2009.0370.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Testing for Thyroid Hormone Concentration after Treatment with Methimazole in Healthy and Hyperthyroid Cats

Abstract: Background: Methimazole suppresses thyroid hormone synthesis and is commonly used to treat feline hyperthyroidism. The degree of variation in thyroid hormone concentrations 24 hours after administration of methimazole and optimal time for blood sampling to monitor therapeutic efficacy have not been determined.Objective: To assess thyroid hormone concentration variation in serum of normal and hyperthyroid cats after administration of methimazole.Animals: Four healthy cats and 889 retrospectively acquired feline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
(44 reference statements)
0
16
0
2
Order By: Relevance
“…Pharmacokinetic studies on cats with hyperthyroidism and normal cats have shown methimazole to have a short half‐life in the plasma (2.3 ± 0.4 hours for cats with hyperthyroidism and 4.7 ± 1.4 hours for normal cats). Moreover, a recent study has shown that there is no relationship between the timing of blood sampling after oral methimazole and the TT4 concentration . Therefore, because methimazole concentrates in the thyroid, plasma methimazole concentrations are unlikely to be correlated with plasma TT4 concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetic studies on cats with hyperthyroidism and normal cats have shown methimazole to have a short half‐life in the plasma (2.3 ± 0.4 hours for cats with hyperthyroidism and 4.7 ± 1.4 hours for normal cats). Moreover, a recent study has shown that there is no relationship between the timing of blood sampling after oral methimazole and the TT4 concentration . Therefore, because methimazole concentrates in the thyroid, plasma methimazole concentrations are unlikely to be correlated with plasma TT4 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…We found that TT4 concentrations remained suppressed for 18–20 hours after (Fig ) treatment with transdermal methimazole, indicating that for this treatment, once daily application is sufficient. These results are similar to a recent study of healthy cats treated with once daily oral methimazole that showed significant suppression of thyroid hormone concentrations for 24 hours …”
Section: Discussionmentioning
confidence: 99%
“…Even though canine thyroid stimulating hormone has a 96% homology with the hormone in cats, a distinction between normal and undetectable values was not found to be always reliable. Today, the value of thyroid stimulating hormone is limited to the exclusion of the disease when a detectable concentration is measured (Wakeling et al, 2008, Rutland et al, 2009.…”
Section: Feline Thyroid Stimulating Hormonementioning
confidence: 99%
“…It begins after two to three weeks and includes measurement of a complete blood count, alkaline phosphatase, alanino-aminotransferase, blood urea nitrogen concentration and creatinine concentration, along with total thyroxine blood concentrations (Trepanier, 2007). Timing of blood sampling is not a significant factor for total thyroxine blood concentration measurement (Rutland et al, 2009;Borreti et al, 2013). If side effects are noted, the drug should be discontinued and another therapeutic option should be pursued (Luyre, 2006).…”
Section: Methimazolementioning
confidence: 99%
“…The bidirectional one-side t test suggests that the bioavailabilities of AH aerosol and injection were identical [7,8].…”
Section: Statistical Analysis Of Bioavailabilitymentioning
confidence: 99%